Mission‐critical open‐source software adoption model validation using Partial Least Square ‐ Structural Equation Modeling. Issue 2 (17th October 2022) - Laila, Umm‐e; Ahmed, Najeed; Arfeen, Asad; Ali, Agha Yasir; Khurram, Mohammad; Khan, Muzammil Ahmed
Abstract: This paper aims to validate the mission‐critical OSS (open‐source software) model acceptance process using a third‐order formative‐formative measuring model. A two‐stage formative‐formative model was used for partial least square analysis. It includes eight primary mission‐critical OSS adoption constructs and three second‐order (technological, organizational, and environmental). Although nomological validity was affirmed, the empirical findings show the absence of multicollinearity. This study will give organizations in critical industries enough information to understand the importance and weight of each component/factor of the mission‐critical OSS adoption model. The coefficient of determination R 2 exceeds the minimum threshold (0.750), and all the hypotheses are significant. This study also contributed to the existing literature by identifying those factors that influence mission‐critical OSS adoption, allowing firms in critical sectors to better understand their mission‐critical OSS adoption issues. Cross‐cultural validation across a broad community is proposed to increase the validity and generalization of the sample scales. Abstract : This paper aims to validate the mission‐critical OSS (open‐source software) model acceptance process using a third‐order formative‐formative measuring model using partial least square analysis structural equation modeling. This study will give organizations in critical industries enough information to understand the importance and weight of each component/factor of the mission‐critical OSS adoption model. The coefficient of determination R 2 exceeds the minimum threshold (0.750), and all the hypotheses are significant.